2012
DOI: 10.1007/bf03262495
|View full text |Cite
|
Sign up to set email alerts
|

Using the Analytic Hierarchy Process to Elicit Patient Preferences

Abstract: The AHP can easily be used to elicit patient preferences and the study has demonstrated differences between patients and experts. The AHP is useful for policy makers in combining multiple clinical outcomes of healthcare interventions grounded in randomized controlled trials in an overall health economic evaluation. This may be particularly relevant in cases where different outcome measures lead to conflicting results about the best alternative to reimburse. Alternatively, AHP may also support researchers in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Basically, the AHP was used to prioritise the importance of the factors in deciding the screening examination. AHP has also been used in combining multiple clinical outcomes of healthcare interventions (Hummel et al, 2012). In order of decreasing importance, the authors found the following outcome measures: response to drug treatment, cognitive function, social function, no anxiety, remission, and no relapse.…”
Section: Ahp In Healthcarementioning
confidence: 99%
“…Basically, the AHP was used to prioritise the importance of the factors in deciding the screening examination. AHP has also been used in combining multiple clinical outcomes of healthcare interventions (Hummel et al, 2012). In order of decreasing importance, the authors found the following outcome measures: response to drug treatment, cognitive function, social function, no anxiety, remission, and no relapse.…”
Section: Ahp In Healthcarementioning
confidence: 99%
“…With high CRs, the judgements are considered as random. The CR has a threshold of 0·2 that should not be exceeded ( Hummel et al . 2012 ).…”
Section: The Studymentioning
confidence: 99%
“…Patients also want to decide scope of service of statutory health insurances’ and which services are covered. Several studies found differences between patients’ and physicians’ perceptions of preferences (e.g., [25]). It is relevant to assess the preferences of the (potential) patients instead of proxy reports.…”
Section: Introductionmentioning
confidence: 99%